Gold medal nutrition - Cardwell, Glenn 1956- (Champaign, Ill. Human Kinetics, 2012)
A practical resource for recreational and elite athletes, coaches and health professionals. Learn how to get enough protein, find the best nutritional supplements, eat to bulk up, travel well, and avoid jet lag, among other subjects.
Sports nutrition principles for athletes. Nutrition and fuel systems for sport ; Protein for growth and maintenance ; Carbohydrate for energy ; Calcium, iron and vitamins for health and performance ; Liquids for hydration, cooling and energy -- Practical sports nutrition for athletes. Food choices for the athlete's kitchen ; Digestion and timing of meals ; What to eat and drink before, during and after exercise ; Nutritional supplements ; Nutrition for vegetarian athletes ; Meal tips for restaurants and road trips -- Weight management for athletes. Muscle building and weight gain strategies ; Fat burning and weight loss strategies ; Nutrition for selected sports.
Keywords: Athletes -- Nutrition